Cutaneous lipomas and macrocephaly as early signs of PTEN hamartoma tumor syndrome. Issue 5 (13th July 2020) - Martin, Hélène; Bessis, Didier; Bourrat, Emmanuelle; Mazereeuw‐Hautier, Juliette; Morice‐Picard, Fanny; Balguerie, Xavier; Chiaverini, Christine; ,
Abstract: Background: The diagnosis of PTEN hamartoma tumor syndrome (PHTS) is difficult in children because they usually do not meet diagnostic criteria. The objective of our study was to characterize lipoma as an early presentation of PHTS. Methods: We performed a retrospective review of children with PHTS diagnosed in French academic hospitals from 2000 to 2019. We included patients presenting at least one lipoma and PTEN‐related disorder confirmed genetically. Results: Thirteen children were included (mean age 5.5 years [range 2.5‐16]). All children had solitary (n = 5) or multiple (n = 8) lipomas, all located on the trunk. Clinical examination revealed macrocephaly in all patients. Genital lentiginosis was found in all patients in whom genitalia were examined (n = 6). Conclusions: In addition to the classical presentation of PHTS with neurological disorders and macrocephaly, some patients, especially the youngest ones, have an initial dermatologic presentation with multiple lipomas. Search for penile freckling and macrocephaly in these patients allows for the diagnosis of PHTS. Lipomatosis should be a major diagnostic criterion in children.